2017
DOI: 10.1038/pr.2017.52
|View full text |Cite
|
Sign up to set email alerts
|

Body composition at birth and its relationship with neonatal anthropometric ratios: the newborn body composition study of the INTERGROWTH-21st project

Abstract: BackgroundWe aimed to describe newborn body composition and identify which anthropometric ratio (weight/length; BMI; or ponderal index, PI) best predicts fat mass (FM) and fat-free mass (FFM).MethodsAir-displacement plethysmography (PEA POD) was used to estimate FM, FFM, and body fat percentage (BF%). Associations between FFM, FM, and BF% and weight/length, BMI, and PI were evaluated in 1,019 newborns using multivariate regression analysis. Charts for FM, FFM, and BF% were generated using a prescriptive subsam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 41 publications
4
87
1
4
Order By: Relevance
“…Current evidence in preterm infants suggests that not only is somatic growth different between the sexes, but body composition differs as well. The intergrowth-21 study concluded that fat mass was higher in girls than boys, even in preterm infants [22]. Lean mass is higher in male preterm infants compared to female preterm infants.…”
Section: Discussionmentioning
confidence: 98%
“…Current evidence in preterm infants suggests that not only is somatic growth different between the sexes, but body composition differs as well. The intergrowth-21 study concluded that fat mass was higher in girls than boys, even in preterm infants [22]. Lean mass is higher in male preterm infants compared to female preterm infants.…”
Section: Discussionmentioning
confidence: 98%
“…Approximately one third of the healthy women who met these criteria were enrolled in the Fetal Growth Longitudinal Study, 1 of the project's 5 studies. This is the cohort from which the fetal growth standards, 1 and the standards for: (1) symphysis-fundal height, 29 (2) gestational weight gain, 30 (3) early pregnancy dating, 2 (4) estimated fetal weight (EFW), 3 (5) newborn body composition, 31 and (6) the postnatal growth of preterm infants were derived, 32 as well as, in 2018, (7) fetal velocity growth and (8) neurodevelopment at 2 years of age. These tools are available as Supplementary Material for clinical use.…”
Section: Methodological Issues Relevant For the Screening Of Fetal Grmentioning
confidence: 99%
“…Phenotypic classification of SGA 69 Phenotypic classification of preterm birth 70 Conceptual issues on preterm birth [71][72][73] Systematic review of novel biomarkers for prediction of spontaneous preterm birth phenotype 74 Newborn size for gestational age and sex from 24 wk' gestation to term 55,75 Systematic review of charts of newborn anthropometry 22 Conceptual issues for preterm standards 76 Systematic review of preterm postnatal charts 23 Preterm postnatal growth: new paradigm 77 Anthropometric protocols, standardization, and quality-control methods for international growth standards 78,79 Newborn body composition and weight for length standards 31 Preterm postnatal growth based on international feeding recommendations 32 Maternal weight gain during pregnancy 30 Systematic review of gestational weight gain charts 80 Postnatal follow-up to age 2 y with neurodevelopmental assessment to evaluate appropriateness of population for creating growth standards 17 Systematic review of differential effects of intrauterine growth restriction on childhood development 81 A simplified multidimensional set of neurodevelopment assessment tools 37 Free e-learning training courses 82,83 Evaluation of dissemination activities 84,85 SGA, small for gestational age. Hence, the INTERGROWTH-21 st project set up its a priori conditions on whether to pool the data sets based on the WHO internationally accepted 3-component strategy used for the WHO child growth standards.…”
Section: Symphysis-fundal Height 29mentioning
confidence: 99%
“…Birth weight and length were measured by trained research nurses within 24 h of delivery for 82 % of neonates. Where assessment within this window was not possiblefor example because of the infant being admitted to the hospital for observationmeasurements were taken within 48 h. Weight: length ratio (WLR; kg/m) was calculated to represent the best anthropometric predictor of neonatal body composition (fat-free mass and fat mass) as described by Villar et al (27) .…”
Section: Maternal Variablesmentioning
confidence: 99%